Structure and Phylogeny of the Curly Birch Chloroplast Genome - Shestibratov, Konstantin A.; Baranov, Oleg Yu.; Mescherova, Eugenia N.; Kiryanov, Pavel S.; Panteleev, Stanislav V.; Mozharovskaya, Ludmila V.; Krutovsky, Konstantin V.; Padutov, Vladimir E. (Frontiers in Genetics, 2021)
Curly birch (Betula pendula var. carelica (Merckl.) Hämet-Ahti) is a relatively rare variety of silver birch (B. pendula Roth) that occurs mainly in Northern Europe and North-West part of Russia (Karelia). It is famous for a beautiful decorative texture of the wood. Abnormal xylogenesis underlying this trait is heritable, but its genetic mechanism has not yet fully understood. The high number of potentially informative genetic markers can be identified through sequencing nuclear and organelle genomes. Here, the de novo assembly, complete nucleotide sequence and annotation of the chloroplast genome (plastome) of curly birch are presented for the first time. The complete plastome length is 160,523 bp. It contains 82 genes encoding structural and enzymatic proteins, 37 tRNAs, and 8 rRNAs. The chloroplast DNA (cpDNA) is AT-rich containing 31.5% of A and 32.5% of T nucleotides. The GC-rich regions represent inverted repeats IR1 and IR2 containing genes of ribosomal (5S, 4.5S, 23S, and 16S) and transport (trnV, trnI, and trnA) RNAs. High content of GC was found in rRNA (55.2%) and tRNA (53.2%) genes, but only 37.0% in protein-coding genes. In total, 384 microsatellite or simple sequence repeat (SSR) loci were found, mostly with mononucleotide motifs (92% of all loci) and predominantly A or T motifs (94% of all mononucleotide motifs). Comparative analysis of cpDNA in different plant species revealed high structural and functional conservatism in organization of the angiosperm plastomes, while the level of differences depends on the phylogenetic relationship. The structural and functional organization of plastome in curly birch was similar to cpDNA in other species of woody plants. Finally, the identified cpDNA sequence variation will allow to develop useful genetic markers.